The Importance of Leadership Behavior and Motivation Ä°n Creating Employee Performance: (A Study at the Faculty of Economics and Business, University of Brawijaya) - Mihrez, Abdo-Alaziz H. E; Thoyib, Armanu (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
This research was conducted at the faculty of economics and business, Brawijaya University which aimed to determine whether there is a direct effect of leadership behavior on intrinsic motivation, extrinsic motivation, and employee performance. In addition, it was done to determine the effect of indirect leadership behavior on employee performance through intrinsic and extrinsic motivation. In this study, the data were collected using a questionnaire with Likert scale, and then distributed to 65 employees UB. To answer the purpose of this study, the method of analysis used was used Partial Least Square (PLS). The results of the analysis in this study inform that leadership behavior has a positive and significant effect on intrinsic motivation, extrinsic motivation, and employee performance. Later in this study it was found that intrinsic motivation variable does not have significant and negative effect on the performance of employees and it is unable to mediate the effect of leadership behavior on employee performance. Meanwhile, extrinsic motivation variable gives positive and significant effect on the performance of employees and it is said that extrinsic motivation is also able to mediate the influence of leadership behaviors on employee performance.